A APLIKASI TRANSITION THEORY TERHADAP ASUHAN KEPERAWATAN PASIEN DIABETES MELLITUS DALAM PERENCANAAN PULANG MODEL LIMALINK-30 - Aulia Finaryati; Herlina; Diah Ratnawati (Jurnal Keperawatan Widya Gantari Indonesia, 2026)
Afaf Ibrahim Meleis's Transition Theory explains responses to health and illness. Transition theory provides a framework for understanding the changes patients experience when transitioning from health to illness and vice versa. This theory provides insights into physical, psychological, and social adjustments. The situational transition from hospital to home requires good discharge planning. This article discusses the application of transition theory to the LIMALink-30 model of discharge planning for patients with diabetes mellitus. The LIMALink-30 model emphasizes patient and family involvement in discharge planning readiness and strengthens motivational interventions to reduce hospital readmission. This article integrates the concepts of the nature of transition, transition conditions and response patterns into a holistic discharge planning. Integrating this model with transition theory helps nurses understand patients' needs in undergoing home care. These findings provide a framework for nurses to manage patients with diabetes mellitus from the time they are admitted to the hospital until they begin treatment at home. This model emphasizes the importance of a well-coordinated care plan. Coordination includes education, emotional support, and ongoing monitoring. The end result is increased patient adherence to treatment and reduced readmission.